Antenatal everolimus therapy for fetal cardiac rhabdomyomas in tuberous sclerosis: A case report of tumor regression and seizure-free neonatal outcome - Malapati, Sai Nikhitha; Malapati, Sai Geethika (Indian Journal of Case Reports, 2025)
We present an exceptionally rare and high-risk scenario of fetal cardiac rhabdomyoma, with the largest lesion postnatally measuring 3 × 2.4 cm size seldom reported in the literature and traditionally associated with severe complications such as outflow obstruction or hydrops. It was detected at 21+6 weeks’ gestation during routine anomaly scanning in a healthy primigravida. Detailed fetal echocardiography revealed three homogeneous, hyperechogenic masses involving the right ventricle and interventricular septum, raising a strong suspicion for tuberous sclerosis complex (TSC). Genetic testing confirmed a pathogenic TSC1 mutation. In a groundbreaking therapeutic intervention, antenatal everolimus was initiated at 24 weeks of gestation, resulting in significant in utero tumor regression-an approach not widely documented. Postnatal management included continuation of Everolimus, serial 2D echocardiographic monitoring showing further mass reduction, and seizure control with phenobarbital initiated based on electrographic seizures detected on electroencephalography. This case not only emphasizes the importance of early antenatal detection but also pioneers the potential of in utero targeted therapy to alter the natural history of genetic syndromes like TSC.